Model tax convention on income and on capital: condensed version, 28 January 2003 - Organisation for Economic Co-operation and Development Committee on Fiscal Affairs (OECD, 2003)
This publication is the condensed version of the OECD Model Tax Convention on Income and on Capital, which is produced in a loose-leaf format to accommodate yearly updates. This fifth edition contains the full text of the Model Tax Convention as it read on 28 January 2003, but without the historical notes, the detailed list of tax conventions between OECD member countries and the background reports that are included in the loose-leaf version.